The Efficacy of a Single Session of 20-Minute Mindful Breathing in Reducing Dyspnea Among Patients With Acute Decompensated Heart Failure: A Randomized Controlled Trial - Ng, Diana Leh-Ching; Chai, Chee-Shee; Tan, Kok-Leng; Chee, Kok-Han; Tung, Yu-Zhen; Wai, Suet-Yen; Teo, Joyce Wei-Ting; Ang, Bin-Ting; Lim, Min-Ai; Tan, Seng-Beng (SAGE publication, 2020)
Heart failure is the leading cause of morbidity and mortality worldwide. Standard treatment for heart failure includes pharmacotherapy and cardiac device implants. However, supportive approaches in managing dyspnea in heart failure are limited. This study aimed to test the efficacy of 20-minute mindful breathing in reducing dyspnea among patients admitted for acute decompensated heart failure. We conducted a parallel-group, non-blinded, randomized controlled trial of a single session of 20-minute mindful breathing plus standard care versus standard care alone among patients admitted for moderate to severe dyspnea due to acute decompensated heart failure, using the dyspnea score based on the Edmonton Symptom Assessment System (ESAS), at the Cardiology Unit of University Malaya Medical Centre in Malaysia. Thirty participants were randomly assigned to a single session of 20-minute mindful breathing plus standard care (n = 15) or standard care alone (n = 15), with no difference in their demographic and clinical characteristics. There was statistically significant reduction in dyspnea in the intervention group compared to the control group at minute 20 (U = 49.5, n1 = 15, n2 =15, median reduction in ESAS dyspnea score 1 = 2, median reduction in ESAS dyspnea score 2 = 0, mean rank 1 = 11.30, mean rank 2 = 19.70, z = −2.692, r = 0.4, P = 0.007). Our results provided evidence that a single session of 20-minute mindful breathing was efficacious in reducing dyspnea for patients admitted for acute decompensated heart failure.